Pengaruh Penambahan Bubuk Gypsum Pada Tanah Lempung Terhadap Uji California Bearing Ratio (CBR) - Desgian Malle’ Pangadongan; Rais Rachman; Irwan Lie Keng Wong (Program Studi Teknik Sipil UKI Paulus-Makassar, 2020)
In Indonesia, there are many building constructions with poor soil condition. Therefore, the land needs to be stabilized in order to meet the necessary technical requirements. One method of improvement is adding chemical mixing materials such as gypsum. One of the parameters that can be seen on good soil soil is bearing capacity. The bearing capacity of the soil can be determined by testing the California Bearing Ratio (CBR). Aims of this study was to determine the physical properties of clay soil and to analyse the effect off adding gypsum powder to clay soil on the CBR Value. The results of the research are the largest CBR value occurred in soil samples mixed with gypsum powder as much as 8% where point 1 the CBR value was 5,67% and point 2 was 4,13%.